Regional histories of development and security seguridad: À la Americana - Fiona Wilson (Danish Institute for International Studies (DIIS), 2005)
The argument of this paper is that there is nothing new about the political connection made between development and security. This has characterized US relations with Latin America grounded in the Monroe Doctrine (giving the US right to intervene) that dates back to 1823. The focus here is on the 1960's, the aftermath of the Cuban Revolution, when the securitydevelopment complex was put firmly in place through the build-up of the region's armed forces militaries and an aggressive, anti-communist ideology under the aegis of the US military. In this context, the paper revisits a visionary paper written by the Brazilian economist Celso Furtado in 1966 when in exile, giving his (Latin American) analysis of the securitydevelopment complex and need to react against US economic hegemony, an important strand in dependency theory.
Keywords: 330; Entwicklung; Lateinamerika; USA; Sicherheitspolitik